Relationship between drug application and mortality rate in Chinese older coronary artery disease/chronic heart failure patients with and without low glomerular filtration rate - Shihui Fu; Ping Ping; Ping Ye; Leiming Luo (BMC, 2019)
Abstract Background This analysis was designed to investigate the relationship between drug application and mortality rate in Chinese older coronary artery disease (CAD)/chronic heart failure (CHF) patients with and without low glomerular filtration rate (GFR). Methods All 1050 Chinese hospitalized patients with diagnosed CAD were included in this analysis, and Cox Regression was used to analyze the relationship between drug application and mortality rate after multivariate adjustment. Low GFR was defined as GFR < 60 ml/min/1.73m2. Results There were 372 patients (35.4%) with low GFR in patients with CAD (1050 patients), and 168 patients (51.4%) in patients with CHF (327 patients). In CAD patients without low GFR, clopidogrel [P = 0.028, odds ratio (OR): 0.620, 95% confidence interval (CI): 0.404-0.951] rather than aspirin (P = 0.173) was significantly associated with lower mortality rate. Statins (P < 0.001, OR: 0.287, 95% CI: 0.180-0.456) were significantly associated with lower mortality rate. In CAD patients with low GFR, aspirin, clopidogrel and statins had no significant relationship with mortality rate (P > 0.05 for all). In CHF patients without low GFR, statins were significantly associated with lower mortality rate (P < 0.001, OR: 0.220, 95% CI: 0.098-0.490). In CHF patients with low GFR, statins had no significant relationship with mortality rate (P > 0.05 for all). Conclusion Clopidogrel but not aspirin was beneficial in Chinese older CAD patients without low GFR rather than those with low GFR, and statins benefited for Chinese older CAD/CHF patients without low GFR rather than those with low GFR. These discoveries might offer some help for the therapy of Chinese older patients with cardiovascular/renal diseases.